Nilai Didaktis Pada Novel The Little Price Karya Antonine De Saint Exupery - Anis Rismayanti (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2023)
Children are entrusted with extraordinary capacity, so that in fact to restore in accordance with His fitra should be equipped with character education, that way literature is an educational medium that is able to guide children because a literary work contains didactic value and entertainment for children. The Little Prince larya Antoine De Saint-Exupary is a book loved by readers because it contains didactic value that gives lessons about kindness. The purpose of this study is to describe the didactic values contained in the Novel The Little Prince by Antoine De Saint Exupery. The method used in this study is descriptive analysis, is a descriptive analysis is a combination of two methods, using a way of describing the facts which is then analyzed. The data collection method used in this study is the Listen and Record technique method. Then, the analysis used by analyzing Miles and Huberman model data, namely Data Collecion, Data Reduction, Data Display, Conclusion. The result of this analysis is that in the novel The Little Prince by Antoine De Saint Exupery there is a didactic value in the form of moral values and motivational values described by the characters in the novel. So that this novel deserves to be presented to children so that they are able to learn about the values contained in thenua, especially the moral values.